A construction of subshifts and a class of semigroups - Hamachi, Toshihiro; Krieger, Wolfgang (Ergodic theory and dynamical systems, 2021)
Subshifts with property (A) are constructed from a class of directed graphs. As special cases the Markov-Dyck shifts are shown to have property (A). The semigroups that are associated to R-graph shifts with Property (A) are determined.
Published online by Cambridge university press: 22 January 2020
Gesehen am 13.08.2021